Is Economic Integration a Historical Shock to City-size Distribution? - Sorhun, Engin (Comparative Economic Research. Central and Eastern Europe, 2018)
Based on the assumption that the economic integration process contributes, via market reforms, to the dynamics of the space distribution in candidate countries, this study examines (i) whether agglomeration forces or dispersion forces are dominant; (ii) whether EU-integration causes a structural break to the space distribution over time; (iii) whether EU-integration makes the city-size distribution more even or uneven in eight eastern European Union members (EU–8). To carry out the analysis, the Ziwot-Andrew and Cusum Square tests are used to detect structural breaks; the ARDL Bound test is used to reveal the interaction between long-run and short-run equilibrium; and the Granger test is used to determine the direction of the causality among the variables. The main results are: the integration with the EU (i) caused a structural break to the city-size distribution, (ii) made the city-size distribution more uneven and (iii) stimulated the agglomerating forces over the spreading forces in the EU–8.